INOVASI SALEP VCO ( VIRGIN COCONUT OIL ) TERHADAP PROSES PENYEMBUHAN LUKA DIABETIK - eko julianto; Rivan Firdaus (Poltekkes Kemenkes Kalimantan Timur, 2016)
VCO (virgin coconut oil) is a plant with native habitat in Southeast Asia, is a plant that contains a lot of primary metabolites and secondary metabolites. Is the main content of saturated fatty acids (9.09%), caprylic acid (6.57%), lauric acid (47.38%). The benefits of VCO is as antimicrobial and anti-inflammatory. This paper is a case study done on a diabetic wound in one patient. VCO using a wound care ointment and wound care management using TIME. Evaluation results show performed salve wounds VCO able to retain moisture and reduce the inflammation that accelerates wound healing.